Exoerythrocytic Plasmodium Parasites Secrete a Cysteine Protease Inhibitor Involved in Sporozoite Invasion and Capable of Blocking Cell Death of Host Hepatocytes - Rennenberg, Annika (Public Library of Science, 2010)
Plasmodium parasites must control cysteine protease activity that is critical for hepatocyte invasion by sporozoites, liver stage development, host cell survival and merozoite liberation. Here we show that exoerythrocytic P. berghei parasites express a potent cysteine protease inhibitor (PbICP, P. berghei inhibitor of cysteine proteases). We provide evidence that it has an important function in sporozoite invasion and is capable of blocking hepatocyte cell death. Pre-incubation with specific anti-PbICP antiserum significantly decreased the ability of sporozoites to infect hepatocytes and expression of PbICP in mammalian cells protects them against peroxide- and camptothecin-induced cell death. PbICP is secreted by sporozoites prior to and after hepatocyte invasion, localizes to the parasitophorous vacuole as well as to the parasite cytoplasm in the schizont stage and is released into the host cell cytoplasm at the end of the liver stage. Like its homolog falstatin/PfICP in P. falciparum, PbICP consists of a classical N-terminal signal peptide, a long N-terminal extension region and a chagasin-like C-terminal domain. In exoerythrocytic parasites, PbICP is posttranslationally processed, leading to liberation of the C-terminal chagasin-like domain. Biochemical analysis has revealed that both full-length PbICP and the truncated C-terminal domain are very potent inhibitors of cathepsin L-like host and parasite cysteine proteases. The results presented in this study suggest that the inhibitor plays an important role in sporozoite invasion of host cells and in parasite survival during liver stage development by inhibiting host cell proteases involved in programmed cell death.